O Aprimoramento da infraestrutura do aeroporto de Rio Brilhante/MS na perspectiva do transporte aéreo de pacientes de UTI - Lago, Roberto Morais (2021)
A reflection about the benefits of air transport in the current agribusiness context, industry and mobile pre-hospital care for the city of Rio Brilhante/MS and it´s population, resolves around the absence of appropriate infrastructure in the airport and the growing demand for emergency services in the last years. As a consequence of the growth in the number of acidentes, of urban violance, of the COVID-19 pandemic and the insufficient structuring of the health transport network. The proposed methodology is an analysis of intervention in airport infrastructure at the Rio Brilhante/MS airdrome that suits local needs for transferring patients that require intensive treatments that are not available in the city. Americans regulations were employed to design the dimensions of the runway, as well as the dimensioning of the runningway layers, making possible to idealize an improvement in this means of transport that is still little explored in the city. A runway measuring 1,478 meters long, 30 meters wide and 227 milimeters thick was obteined, meeting the needs for transporting ICU patients.